Sirolimus augments hematopoietic stem and progenitor cell regeneration following hematopoietic insults. (12th December 2020) - Lin, Zenghua; Hollinger, Maile K.; Wu, Zhijie; Sun, Wanling; Batey, Kaylind; Kim, Jisoo; Chen, Jichun; Feng, Xingmin; Young, Neal S.
Abstract: The role of mammalian target of rapamycin and its suppressor sirolimus in the regulation of hematopoietic stem and progenitor cells (HSPCs) is controversial. We show here that sirolimus enhanced regeneration of HSPCs in mice exposed to sublethal total body irradiation (TBI) and other regenerative stressors. Sorted Lin − CD150 + bone marrow cells from sirolimus‐treated TBI mice had increased expression of c‐Kit and other hematopoietic genes. HSPCs from sirolimus‐treated TBI mice were functionally competent when tested by competitive engraftment in vivo. Postradiation regeneration of HSPCs in mice treated with sirolimus was accompanied by decreased γ‐H2AX levels detected by flow cytometry and increased expression of DNA repair genes by quantitative polymerase chain reaction. Reduction of cell death and DNA damage post‐radiation by sirolimus was associated with enhanced clearance of cellular reactive oxygen species (ROS) in HSPCs. Increased HSPC recovery with sirolimus was also observed in mice injected with hematoxic agents, busulfan and 5‐fluorouracil. In contrast, sirolimus showed no effect on HSPCs in normal mice at steady state, but stimulated HSPC expansion in mice carrying the Wv mutation at the c‐Kit locus. In human to mouse xenotransplantation, sirolimus enhanced engraftment of irradiated human CD34 + cells. In summary, our results are consistent with sirolimus' acceleration of HSPC recovery in response to hematopoietic stress, associated with reduced DNA damage and ROS. Sirolimus might have clinical application for the treatment and prevention of hematopoietic injury. Abstract : Sirolimus accelerates hematopoietic stem and progenitor cell recovery in response to hematopoietic stress, which is associated with reduced DNA damage and reactive oxygen species.